Silica nanoparticle emulsion flame retardant, preparation method and application thereof
Patent Information
- Application Number
- CN202611138173.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-16
AI Technical Summary
普通阻燃剂常因稳定性不足而丧失作用,形成新的煤氧接触,如何保证阻燃效率前提下延长阻燃剂使用寿命,成为当前阻燃剂研究的热点
[0092](1)本发明提供的二氧化硅纳米粒子乳液阻燃剂能够形成稳定的乳液阻燃薄膜,具有优异且稳定、长效的阻燃性能,且安全性较高,其中,二氧化硅纳米粒子乳液阻燃剂的阻燃率≥45%,即使在放置一段时间后使用,其阻燃率依旧能够达到40%以上;
Smart Images

Figure CN122917801A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of emulsion flame retardant technology, specifically relating to a silica nanoparticle emulsion flame retardant, its preparation method, and its application. Background Technology
[0002] Currently, the situation regarding coal mine safety is extremely serious. Spontaneous combustion of coal is one of the main causes of mine fires, easily leading to enormous losses. The essence of spontaneous combustion is the interaction between coal and oxygen. Flame retardants inhibit coal oxidation by preventing coal-oxygen contact and reducing the low-temperature oxidizing activity of coal. Currently, commonly used flame retardants are mainly physical or chemical. Physical flame retardants primarily work by coating the coal surface to form a protective layer, preventing coal-oxygen contact; chemical flame retardants react with the active groups on the coal surface to generate relatively stable transition products, inhibiting the chemical adsorption of coal oxidation. Ordinary flame retardants often lose their effectiveness due to insufficient stability, creating new coal-oxygen contact. How to extend the service life of flame retardants while ensuring flame retardant efficiency has become a current research hotspot.
[0003] Commonly used physical flame retardants include gel flame retardants, polymer flame retardants, and foam flame retardants. Gel flame retardants can penetrate into the crevices of coal samples, inhibiting spontaneous combustion by isolating oxygen and blocking air leaks. However, gels have poor fluidity, are prone to clogging, and have high production costs. Polymer flame retardants mainly function to cool and lower the temperature, but their thermal stability is poor, and they can also act as catalysts at high temperatures, promoting spontaneous combustion of coal. Foam flame retardants cover the surface of coal samples, isolating them from air, but foam is unstable and covers the coal surface for a short time. Chemical flame retardants mainly utilize the fact that they first react chemically with the active groups generated during the low-temperature oxidation of coal, terminating the free radical chain reaction and thus inhibiting the coal oxidation reaction. However, chemical flame retardants produce harmful gases during the process of inhibiting coal oxidation.
[0004] Therefore, there is a need for a new type of flame retardant that is highly safe, has excellent flame retardancy, and a long flame retardant life to meet application requirements. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a silica nanoparticle emulsion flame retardant, its preparation method, and its application.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a silica nanoparticle emulsion flame retardant, comprising: a modified silica nanoparticle aqueous phase, a magnesium hydroxide nanoparticle aqueous phase, and an oil phase containing a crosslinking agent.
[0008] Current physical flame retardants work by covering the coal surface to block oxygen, while chemical flame retardants work by reacting with active groups in the coal to interrupt the oxidation chain. However, both types of flame retardants suffer from insufficient stability and short action time. Therefore, this invention provides a silica nanoparticle emulsion flame retardant that combines the advantages of both physical and chemical flame retardants, as detailed below:
[0009] This invention uses modified silica nanoparticles and magnesium hydroxide nanoparticles as raw materials to self-assemble and construct Janus particles to prepare stable Pickering emulsion flame retardants. In this structure, the chemically stable silica nanoparticles mainly function to construct a continuous and dense physical barrier layer on the surface of the coal, continuously blocking oxygen; while the magnesium hydroxide particles decompose when the coal temperature rises, absorbing heat and releasing non-combustible gases, thereby exerting a chemical inhibition effect. The modified silica nanoparticles and magnesium hydroxide nanoparticles are tightly combined at the nanoscale, achieving simultaneous and long-lasting physical coverage and chemical inhibition.
[0010] Therefore, the silica nanoparticle emulsion flame retardant provided by this invention can form a stable emulsion flame retardant film, which has excellent, stable and long-lasting flame retardant properties and high safety. It provides a new idea for the application of flame retardants in the prevention and control of spontaneous combustion of coal, and also provides a useful reference for the development of safe, economical and stable flame retardants.
[0011] In some embodiments, the particle size D50 of the modified silica nanoparticles is 10-500 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 200 nm, 350 nm, 500 nm or any of the above values, preferably 10-100 nm.
[0012] In some embodiments, the modified silica nanoparticles are surface-modified silica nanoparticles, preferably the surface modifiers include 3-aminopropyltriethoxysilane and / or 3-glycidoxypropyltrimethoxysilane.
[0013] In some embodiments, the concentration of the aqueous phase of the modified silica nanoparticles is 1-25 wt%, for example, 1 wt%, 4 wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, or any of the above values, preferably 3.5-11.5 wt%.
[0014] In some embodiments, the particle size D50 of the magnesium hydroxide nanoparticles is 10-500 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 200 nm, 350 nm, 500 nm or any range between the above values, preferably 10-100 nm.
[0015] In some embodiments, the aqueous phase of the magnesium hydroxide nanoparticles further includes a dispersion medium, preferably the dispersion medium comprising any one or a combination of at least two of sodium alginate, chitosan, or polyethyleneimine.
[0016] In some embodiments, the mass ratio of the modified silica nanoparticles to magnesium hydroxide nanoparticles is 1:(0.1-10), for example 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:10 or any of the above values, preferably 1:(0.4-8), and more preferably 1:(2-4).
[0017] In some embodiments, the crosslinking agent includes any one or a combination of at least two of adipoyl chloride, phthaloyl chloride, isophthaloyl chloride, or terephthaloyl chloride, preferably terephthaloyl chloride.
[0018] In some embodiments, the concentration of the crosslinking agent in the oil phase containing the crosslinking agent is 0.1-5 wt%, for example, 0.1 wt%, 0.6 wt%, 1.1 wt%, 1.8 wt%, 2.4 wt%, 3.0 wt%, 3.6 wt%, 4.2 wt%, 4.7 wt%, 5 wt%, or any of the above values.
[0019] In some embodiments, the oil phase comprises any one or a combination of at least two of silicone oil, toluene, n-hexane, or cyclohexane, preferably cyclohexane.
[0020] In some embodiments, the total volume ratio of the aqueous phase of the modified silica nanoparticles and the aqueous phase of the magnesium hydroxide nanoparticles to the volume ratio of the oil phase containing the crosslinking agent is 1:(1-20), for example 1:1, 1:3, 1:4, 1:6, 1:9, 1:12, 1:14, 1:16, 1:18, 1:20 or any of the above values, preferably 1:(2-5).
[0021] In some embodiments, the flame retardancy of the silica nanoparticle emulsion flame retardant is ≥40%, for example, 45%, 50%, 51%, 52%, 53%, 55%, 56%, 58%, 60%, 62%, 65%, 67%, 68%, 70%, 72% or any of the above values, preferably ≥45%, and more preferably ≥53%.
[0022] In this invention, the method for testing the flame retardancy rate includes:
[0023] Coal samples with particle sizes ranging from 0.1 to 20 mm were weighed and mixed to prepare experimental coal samples. A silica nanoparticle emulsion flame retardant was sprayed onto the coal samples for blending. A programmed temperature rise experiment was used to test the flame retardant rate of the coal samples. The prevention of spontaneous combustion of coal was mainly achieved by inhibiting it during the early low-temperature oxidation stage. CO was used as the indicator gas. The programmed temperature was set to 150℃, and the heating rate was 1-3℃ / min. The flame retardant rate of the coal sample was calculated as: (CO release from untreated coal sample - CO release from flame retardant-treated coal sample) ÷ CO release from untreated coal sample × 100%.
[0024] The mass ratio of the coal sample to the silica nanoparticle emulsion flame retardant is 1:(0.1-0.5), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or any of the above values.
[0025] In a second aspect, the present invention provides a method for preparing a silica nanoparticle emulsion flame retardant as described in the first aspect, the method comprising:
[0026] The modified silica nanoparticle aqueous phase, magnesium hydroxide nanoparticle aqueous phase, and oil phase containing a crosslinking agent are mixed and reacted. After the reaction, excess liquid is removed to obtain the silica nanoparticle emulsion flame retardant.
[0027] In some embodiments, the reaction method includes sonicating for 0.5-2 h (e.g., 0.5 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.4 h, 1.5 h, 1.7 h, 1.8 h, 2 h or any range of the above values) at room temperature.
[0028] In the preparation method described in this invention, the modified silica nanoparticles and magnesium hydroxide nanoparticles self-assemble to form Janus particles to prepare a stable Pickering emulsion flame retardant. In the presence of a crosslinking agent, the modified silica nanoparticles and magnesium hydroxide nanoparticles are oriented and covalently linked at the oil-water interface to form a structurally stable dumbbell-shaped Janus particle. The Janus particle is amphiphilic and can act as a highly efficient solid emulsifier to stabilize the oil and water phases, thereby forming a stable Pickering emulsion as a silica nanoparticle emulsion flame retardant, solving the problem of poor stability of traditional flame retardants.
[0029] The preparation method provided by this invention is simple to operate, uses readily available raw materials, and is inexpensive, providing a foundation for the development of safe, economical, and stable flame retardants.
[0030] In some embodiments, the preparation method of the silica nanoparticles is a sol-gel method, preferably including: hydrolysis and condensation of tetraethyl orthosilicate under an alkaline catalyst to obtain the silica nanoparticles.
[0031] In some embodiments, the method for preparing the silica nanoparticles includes:
[0032] S11. Mix high-purity water, ethanol (EtOH), and concentrated ammonia to obtain a homogeneous alkaline solution;
[0033] S12. Tetraethyl orthosilicate is dissolved in ethanol to obtain a tetraethyl orthosilicate solution;
[0034] S13. With stirring, the tetraethyl orthosilicate solution is added dropwise to the alkaline solution. After the addition is complete, the reaction is continued with stirring until the solution turns milky white.
[0035] S14. Centrifuge and wash to obtain the silica nanoparticles.
[0036] In some embodiments, the mass ratio of concentrated ammonia, high-purity water, and ethanol is 1:(2-7):(5-20), where 2-7 can be 2, 2.5, 3, 4, 4.5, 5, 5.5, 6, 6.5, 7, or any of the above values, and 5-20 can be 5, 7, 9, 11, 13, 15, 16, 17, 19, 20, or any of the above values, preferably 1:(2.4-6.8):(5.4-18.2).
[0037] In some embodiments, the mixing temperature is 20-45°C, for example 20°C, 23°C, 25°C, 28°C, 30°C, 35°C, 38°C, 40°C, 43°C, 45°C or any of the above values, and the stirring rate is 100-500 r / min, for example 100 r / min, 140 r / min, 180 r / min, 230 r / min, 270 r / min, 320 r / min, 360 r / min, 410 r / min, 450 r / min, 500 r / min or any of the above values.
[0038] In some embodiments, in step S12, the mass ratio of tetraethyl orthosilicate to ethanol is 1:(1-12), for example 1:1, 1:2, 1:3, 1:5, 1:6, 1:8, 1:9, 1:10, 1:11, 1:12 or any of the above values, preferably 1:(1.2-10.8).
[0039] In some embodiments, the mass ratio of tetraethyl orthosilicate to concentrated ammonia is (0.1-1):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or any range between the above values.
[0040] In some embodiments, the dripping is slow, preferably for a time of 20-90 min, such as 20 min, 25 min, 30 min, 40 min, 50 min, 60 min, 65 min, 70 min, 80 min, 90 min, or any range of the above values.
[0041] In some embodiments, after the addition is complete, the reaction continues. Preferably, the temperature for continued reaction is 30-50°C, for example, 30°C, 32°C, 35°C, 37°C, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, or any range of the above values. The rotation speed is 100-500 r / min, for example, 100 r / min, 140 r / min, 180 r / min, 230 r / min, 270 r / min, 320 r / min, 360 r / min, 410 r / min, 450 r / min, 500 r / min, or any range of the above values. The reaction time is 2-8 h, for example, 2 h, 2.6 h, 3 h, 4 h, 4.5 h, 5 h, 6 h, 6.5 h, 7 h, 8 h, or any range of the above values.
[0042] In some embodiments, the centrifugation speed is 8000-12000 rpm, such as 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm, 10000 rpm, 10500 rpm, 11000 rpm, 11500 rpm, 12000 rpm or any of the above values, and the time is 2-10 min, such as 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 5 min, 7 min, 8 min, 9 min, 10 min or any of the above values.
[0043] In some embodiments, the washing method involves washing the product with EtOH and high-purity water alternately 2-5 times, for example, 2 times, 3 times, 4 times, 5 times or any range between the above values, to remove unreacted raw materials.
[0044] In some embodiments, the method for preparing the silica nanoparticles includes:
[0045] In some embodiments, the method for preparing the modified silica nanoparticles includes: mixing silica nanoparticles with a surface modifier and reacting them to obtain the modified silica nanoparticles.
[0046] In some embodiments, the method for preparing the modified silica nanoparticles includes:
[0047] S21. Silica nanoparticles are added to a dispersion medium and dispersed to obtain a dispersion.
[0048] S22. Under stirring, the surface modifier is added dropwise to the dispersion. After the addition, the stirring reaction continues. After the reaction, the mixture is centrifuged, washed, and dried to obtain the modified silica nanoparticles.
[0049] In some embodiments, the dispersion medium comprises any one or a combination of at least two of toluene, xylene, cyclohexane or n-heptane, preferably toluene and / or xylene.
[0050] In some embodiments, the concentration of the dispersion is 0.1-10 wt%, for example 0.1 wt%, 1.2 wt%, 2 wt%, 3 wt%, 4.5 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 10 wt%, or any of the above values.
[0051] In some embodiments, the stirring rate is 100-500 r / min, for example 100 r / min, 140 r / min, 180 r / min, 230 r / min, 270 r / min, 320 r / min, 360 r / min, 410 r / min, 450 r / min, 500 r / min or any range between the above values.
[0052] In some embodiments, the surface modifier comprises 3-aminopropyltriethoxysilane (APTES) and / or 3-glycidoxypropyltrimethoxysilane (GPTMS), preferably a combination of APTES and GPTMS, more preferably a mass ratio of GPTMS to APTES of 1:(0.1-2), such as 1:0.1, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or any range of the above values, and even more preferably 1:(0.45-1.92).
[0053] This invention modifies silica nanoparticles by introducing surface modifiers, enabling the grafting of active functional groups such as amino and epoxy groups onto the surface of silica nanoparticles, providing reaction sites for subsequent covalent bonding with magnesium hydroxide particles.
[0054] In some embodiments, the mass ratio of the surface modifier to the tetraethyl orthosilicate is (0.1-15):1, for example, 0.1:1, 1.5:1, 3:1, 4.5:1, 6:1, 8:1, 10:1, 12:1, 13.5:1, 15:1 or any range of the above values, preferably (0.4-12):1.
[0055] In some embodiments, the temperature at which the stirring reaction continues after the droplet addition is 65-90°C, for example, 65°C, 70°C, 72°C, 75°C, 77°C, 80°C, 83°C, 86°C, 88°C, 90°C or any range of the above values, and the time is 4-12 hours, for example, 4 hours, 4.5 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, 10 hours, 12 hours or any range of the above values.
[0056] In some embodiments, the centrifugation speed is 8000-12000 rpm, such as 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm, 10000 rpm, 10500 rpm, 11000 rpm, 11500 rpm, 12000 rpm or any of the above values, and the time is 10-40 min, such as 10 min, 14 min, 18 min, 22 min, 26 min, 30 min, 33 min, 36 min, 38 min, 40 min or any of the above values.
[0057] In some embodiments, the drying temperature is 40-80°C, for example 40°C, 44°C, 48°C, 50°C, 56°C, 60°C, 66°C, 70°C, 75°C, 80°C or any range of the above values, and the drying time is 4-6 h, for example 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.7 h, 6 h or any range of the above values.
[0058] In some embodiments, the washing method is to wash the product with EtOH 2-5 times, for example 2 times, 3 times, 4 times, 5 times or any range between the above values, to remove unreacted raw materials.
[0059] In some embodiments, the method for preparing modified silica nanoparticles includes:
[0060] In some embodiments, the preparation method of the magnesium hydroxide nanoparticles is a liquid-phase coprecipitation method, preferably including: reacting magnesium chloride hexahydrate and sodium hydroxide to obtain the magnesium hydroxide nanoparticles.
[0061] In some embodiments, the method for preparing the magnesium hydroxide nanoparticles includes:
[0062] Magnesium chloride hexahydrate and sodium hydroxide were dissolved in high-purity water and reacted with vigorous stirring. After the reaction, the mixture was centrifuged and washed to obtain the magnesium hydroxide nanoparticles.
[0063] In some embodiments, the mass ratio of magnesium chloride hexahydrate to sodium hydroxide is (1-5):1, for example 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 4.8:1, 5:1 or any of the above values, preferably (1.3-4.3):1.
[0064] In some embodiments, the stirring rate of the reaction is 1000-1200 r / min, for example 1000 r / min, 1020 r / min, 1040 r / min, 1060 r / min, 1080 r / min, 1100 r / min, 1130 r / min, 1150 r / min, 1170 r / min, 1200 r / min or any range between the above values; the temperature is 70-95℃, for example 70℃, 73℃, 76℃, 80℃, 82℃, 85℃, 88℃, 90℃, 93℃, 95℃ or any range between the above values; and the time is 1.5-4 h, for example 1.5 h, 1.8 h, 2.1 h, 2.4 h, 2.7 h, 3 h, 3.2 h, 3.5 h, 3.7 h, 4 h or any range between the above values.
[0065] In some embodiments, the washing method includes washing with high-purity water 5-8 times (e.g., 5, 6, 7, 8 times or any range of the above values) and then washing with EtOH 3-6 times (e.g., 3, 4, 5, 6 times or any range of the above values).
[0066] In some embodiments, the method for preparing the magnesium hydroxide nanoparticles includes:
[0067] In some embodiments, the method further includes preparing a magnesium hydroxide nanoparticle dispersion. Preferably, the preparation method of the magnesium hydroxide nanoparticle dispersion includes: mixing magnesium hydroxide nanoparticles and a dispersion medium in water to obtain the magnesium hydroxide nanoparticle dispersion. More preferably, the magnesium hydroxide nanoparticles are dispersed in an aqueous solution of the dispersion medium.
[0068] In some embodiments, the aqueous solution of the dispersion medium is preferably a weakly acidic aqueous solution of the dispersion medium, wherein the pH value of the weakly acidic aqueous solution is less than 6.5, for example, 6.4, 6.3, 6.2, 6, 5.8, 5.5, 5 or any of the above values. By controlling the aqueous solution to be weakly acidic, the present invention can improve the solubility of the dispersion medium.
[0069] In some embodiments, the weak acid used in the weak acid aqueous solution is any one or a combination of at least two of glacial acetic acid, formic acid, or hydrochloric acid, preferably glacial acetic acid.
[0070] In some embodiments, the aqueous solution of the dispersion medium includes the dispersion medium and glacial acetic acid, preferably the mass ratio of the dispersion medium to glacial acetic acid is 1:(0.95-1.05), for example 1:0.95, 1:0.98, 1:1, 1:1.01, 1:1.02, 1:1.04, 1:1.05 or any range between the above values.
[0071] In some embodiments, the dispersion medium comprises any one or a combination of at least two of sodium alginate, chitosan, or polyethyleneimine.
[0072] This invention introduces a dispersion medium with active functional groups such as amino and hydroxyl groups, which can coat the surface of magnesium hydroxide nanoparticles, giving the magnesium hydroxide nanoparticles the ability to covalently crosslink.
[0073] In some embodiments, the concentration of the dispersion medium in the aqueous solution of the dispersion medium is 0.1-1 wt%, for example 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, or any of the above values, preferably 0.2-0.6 wt%.
[0074] In some embodiments, the concentration of magnesium hydroxide nanoparticles in the magnesium hydroxide nanoparticle dispersion is 1-10 wt%, for example, 1 wt%, 1.5 wt%, 2 wt%, 1.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, or any of the above values, preferably 1-5 wt%.
[0075] In some embodiments, the preparation method of the magnesium hydroxide nanoparticle dispersion includes:
[0076] In some embodiments, the method for preparing the aqueous phase of magnesium hydroxide nanoparticles includes: mixing a magnesium hydroxide nanoparticle dispersion with high-purity water to obtain the aqueous phase of magnesium hydroxide nanoparticles.
[0077] In some embodiments, the method for preparing the modified silica nanoparticle aqueous phase includes: dispersing modified silica nanoparticles in high-purity water to obtain the modified silica nanoparticle aqueous phase.
[0078] In some embodiments, the preparation method of the silica nanoparticle emulsion flame retardant includes:
[0079] S1. At 20-45℃ and 100-500 r / min, concentrate ammonia, high-purity water and ethanol were mixed in a mass ratio of 1:(2-7):(5-20) to obtain an alkaline solution. Tetraethyl orthosilicate was dissolved in ethanol in a mass ratio of 1:(1-12) to prepare a tetraethyl orthosilicate solution. Stirring was continued. The tetraethyl orthosilicate solution was added dropwise to the alkaline solution in a mass ratio of tetraethyl orthosilicate to concentrate ammonia of (0.1-1):1, with a dropwise addition time of 20-90 min. After the addition was completed, the reaction was stirred at 30-50℃ and 100-500 r / min for 2-8 h until the solution turned milky white. The solution was centrifuged at 8000-12000 rpm for 2-10 min. The product was washed 2-5 times alternately with EtOH and high-purity water to obtain silica nanoparticles.
[0080] S2. Silica nanoparticles were dispersed in a dispersion medium to obtain a dispersion with a concentration of 0.1-10 wt%. The surface modifier was added dropwise to the dispersion at a mass ratio of (0.5-15):1 to tetraethyl orthosilicate at 100-500 r / min. After the addition was complete, the reaction temperature was maintained at 65-90℃ and the reaction continued for 4-12 h. After the reaction was completed, the mixture was centrifuged at 8000-12000 rpm for 10-40 min. The product was washed 2-5 times with EtOH and dried in a vacuum environment at 40-80℃ for 4-6 h to obtain modified silica nanoparticles.
[0081] S3. At 1000-1200 r / min, magnesium chloride hexahydrate and sodium hydroxide were mixed at a mass ratio of (1-5):1, and stirred at 70-95℃ for 1.5-4 h. After the reaction was completed, the mixture was centrifuged at 8000-12000 rpm for 2-10 min. The product was washed 5-8 times with high-purity water and then washed 3-6 times with EtOH to obtain magnesium hydroxide nanoparticles.
[0082] S4. With a concentration of 1-10 wt% for magnesium hydroxide nanoparticles, magnesium hydroxide nanoparticles are ultrasonically dispersed in an aqueous solution of 0.1-1 wt% dispersion medium to obtain a magnesium hydroxide nanoparticle dispersion.
[0083] S5. At room temperature, modified silica nanoparticles are dispersed in high-purity water to obtain an aqueous phase of modified silica nanoparticles with a concentration of 1-25 wt%; magnesium hydroxide nanoparticle dispersion is dispersed in high-purity water to obtain an aqueous phase of magnesium hydroxide nanoparticles with a concentration of 1-5 wt%.
[0084] The modified silica nanoparticles and magnesium hydroxide nanoparticles were mixed with an oil phase containing 0.1-5 wt% crosslinking agent at a mass ratio of 1:(0.1-10), and the total volume ratio of the aqueous phase of modified silica nanoparticles and the aqueous phase of magnesium hydroxide nanoparticles to the volume ratio of the oil phase containing the crosslinking agent was 1:(1-20). The mixture was then sonicated for 0.5-2 h. After sonication, excess liquid phase (liquid, solvent) was removed to obtain the silica nanoparticle emulsion flame retardant.
[0085] In step S5, modified silica nanoparticles and magnesium hydroxide nanoparticles come into contact with a bifunctional crosslinking agent at the oil-water interface, reacting with the active functional groups on their surfaces to covalently link the two particles at the interface, forming Janus particles with an asymmetric structure. This invention utilizes ultrasound to enable the particles to fully contact and react at the interface, while the formed Janus particles act as solid particle emulsifiers to disperse the system and form a stable Pickering emulsion.
[0086] Thirdly, the present invention provides an application of the silica nanoparticle emulsion flame retardant as described in the first aspect in coal spontaneous combustion prevention and extinguishing materials.
[0087] The present invention also provides a method for applying the silica nanoparticle emulsion flame retardant, the method comprising:
[0088] The silica nanoparticle emulsion flame retardant can be sprayed directly onto the surface of coal, or diluted before spraying.
[0089] In some embodiments, the particle size of the coal is 0.1-20 mm, for example 0.1 mm, 0.5 mm, 1 mm, 2 mm, 5 mm, 8 mm, 10 mm, 12 mm, 15 mm, 18 mm, 20 mm or any of the above values.
[0090] In some embodiments, the dilution factor is 0.01-5 times, for example 0.01 mm, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm or any range of the above values.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] (1) The silica nanoparticle emulsion flame retardant provided by the present invention can form a stable emulsion flame retardant film, which has excellent, stable and long-lasting flame retardant properties and high safety. The flame retardant rate of the silica nanoparticle emulsion flame retardant is ≥45%, and even after being placed for a period of time, its flame retardant rate can still reach more than 40%.
[0093] (2) The preparation method provided by the present invention is simple to operate, the raw materials are readily available, and the cost is low, which provides a basis for the development of safe, economical and stable flame retardants. Attached Figure Description
[0094] Figure 1 The image shows the morphology of the silica nanoparticle emulsion flame retardant prepared in Example 1. Detailed Implementation
[0095] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0096] Unless otherwise specified, the raw materials involved in the following specific embodiments of the present invention are all conventional materials in the art, and can be purchased from commercially available products. Some raw material information is as follows:
[0097] TEOS, magnesium chloride hexahydrate, cyclohexane, and terephthaloyl chloride were all purchased from Aladdin.
[0098] Concentrated ammonia and sodium hydroxide were purchased from Sinopharm, and GPTMS and APTES were purchased from Maclean's.
[0099] Chitosan: Purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a low viscosity of <100 mpa•s and a degree of deacetylation ≥90%;
[0100] Example 1
[0101] This embodiment provides a method for preparing a silica nanoparticle emulsion flame retardant, as follows:
[0102] S1. At 30℃ and 300 r / min, concentrated ammonia, high-purity water and ethanol were mixed in a mass ratio of 1:3:6 to obtain an alkaline solution. Tetraethyl orthosilicate was dissolved in ethanol in a mass ratio of 1:4 to prepare a tetraethyl orthosilicate solution. Stirring was continued. The tetraethyl orthosilicate solution was added dropwise to the alkaline solution in a mass ratio of tetraethyl orthosilicate to concentrated ammonia of 0.5:1 over a period of 30 min. After the addition was completed, the reaction was stirred at 40℃ and 350 r / min for 6 h until the solution turned milky white. The solution was centrifuged at 9000 rpm for 4 min. The product was washed four times with EtOH and high-purity water alternately to obtain silica nanoparticles.
[0103] S2. Silica nanoparticles were dispersed in a dispersion medium to obtain a dispersion with a concentration of 1 wt%. At a mass ratio of 0.48:1 between the surface modifier and tetraethyl orthosilicate, the surface modifier (GPTMS:APTES mass ratio = 2:1) was added dropwise to the dispersion at 300 r / min. After the addition was complete, the reaction temperature was maintained at 80℃ for 8 h. After the reaction was completed, the mixture was centrifuged at 9000 rpm for 30 min. The product was washed four times with EtOH and dried in a vacuum environment at 60℃ for 5 h to obtain modified silica nanoparticles.
[0104] S3. At 1500 r / min, magnesium chloride hexahydrate and sodium hydroxide were mixed at a mass ratio of 2.5:1 and stirred at 85℃ for 1.5 h. After the reaction was completed, the mixture was centrifuged at 9000 rpm for 5 min. The product was washed 6 times with high-purity water and then 3 times with EtOH to obtain magnesium hydroxide nanoparticles.
[0105] S4. With a concentration of 4 wt% for magnesium hydroxide nanoparticles, magnesium hydroxide nanoparticles were ultrasonically dispersed in an aqueous solution of 0.5 wt% dispersion medium (chitosan) to obtain a magnesium hydroxide nanoparticle dispersion.
[0106] S5. At room temperature, modified silica nanoparticles were dispersed in high-purity water to obtain an aqueous phase of modified silica nanoparticles with a concentration of 5 wt%; magnesium hydroxide nanoparticle dispersion was dispersed in high-purity water to obtain an aqueous phase of magnesium hydroxide nanoparticles with a concentration of 1 wt%.
[0107] The modified silica nanoparticles and magnesium hydroxide nanoparticles were mixed with an oil phase containing 0.21 wt% crosslinking agent (terephthaloyl chloride) at a mass ratio of 1:3, and the total volume ratio of the aqueous phase of modified silica nanoparticles and the aqueous phase of magnesium hydroxide nanoparticles to the volume ratio of the oil phase containing the crosslinking agent was 1:2.5. The mixture was then sonicated for 1.5 h. After sonication, excess liquid was removed to obtain a silica nanoparticle emulsion flame retardant.
[0108] Examples 2-5
[0109] This embodiment provides a method for preparing a silica nanoparticle emulsion flame retardant.
[0110] The difference from Example 1 is that in this example, the mass ratio of modified silica nanoparticles to magnesium hydroxide nanoparticles is 1:0.3 (Example 2), 1:1 (Example 3), 1:8 (Example 4), and 1:10 (Example 5).
[0111] Example 6
[0112] This embodiment provides a method for preparing a silica nanoparticle emulsion flame retardant.
[0113] The difference from Example 1 is that in this example, the crosslinking agent is isophthaloyl chloride.
[0114] Example 7
[0115] This embodiment provides a method for preparing a silica nanoparticle emulsion flame retardant, as follows:
[0116] S1. At 25℃ and 500 r / min, concentrated ammonia, high-purity water, and ethanol were mixed in a mass ratio of 1:2.4:18.2 to obtain an alkaline solution. Tetraethyl orthosilicate was dissolved in ethanol in a mass ratio of 1:1.2 to prepare a tetraethyl orthosilicate solution. The mixture was stirred continuously. The tetraethyl orthosilicate solution was added dropwise to the alkaline solution in a mass ratio of 1:1 for 90 min. After the addition was complete, the mixture was stirred at 30℃ and 100 r / min for 2 h until the solution turned milky white. The mixture was centrifuged at 8000 rpm for 10 min. The product was washed twice with EtOH and high-purity water alternately to obtain silica nanoparticles.
[0117] S2. Silica nanoparticles were dispersed in a dispersion medium to obtain a dispersion with a concentration of 0.1 wt%. At a mass ratio of surface modifier to tetraethyl orthosilicate of 0.48:1, the surface modifier (GPTMS:APTES mass ratio = 1:0.45) was added dropwise to the dispersion at 100 r / min. After the addition was complete, the reaction temperature was maintained at 65℃ for 12 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 40 min. The product was washed twice with EtOH and dried in a vacuum environment at 40℃ for 6 h to obtain modified silica nanoparticles.
[0118] S3. At 1500 r / min, magnesium chloride hexahydrate and sodium hydroxide were mixed at a mass ratio of 1.3:1 and stirred at 70℃ for 4 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 10 min. The product was washed 5 times with high-purity water and then 6 times with EtOH to obtain magnesium hydroxide nanoparticles.
[0119] S4. With a concentration of 1 wt% for magnesium hydroxide nanoparticles, magnesium hydroxide nanoparticles were ultrasonically dispersed in an aqueous solution of 0.2 wt% dispersion medium (chitosan) to obtain a magnesium hydroxide nanoparticle dispersion.
[0120] S5. At room temperature, the modified silica nanoparticles were dispersed in high-purity water to obtain an aqueous phase of modified silica nanoparticles with a concentration of 3.5 wt%.
[0121] The modified silica nanoparticles and magnesium hydroxide nanoparticles were mixed with an oil phase containing 0.1 wt% crosslinking agent (terephthaloyl chloride) at a mass ratio of 1:3, and the total volume ratio of the aqueous phase of modified silica nanoparticles and the aqueous phase of magnesium hydroxide nanoparticles to the volume ratio of the oil phase containing the crosslinking agent was 1:5. The mixture was then sonicated for 0.5 h. After sonication, excess liquid was removed to obtain a silica nanoparticle emulsion flame retardant.
[0122] Example 8
[0123] This embodiment provides a method for preparing a silica nanoparticle emulsion flame retardant, as follows:
[0124] S1. At 45℃ and 100 r / min, concentrated ammonia, high-purity water, and ethanol were mixed in a mass ratio of 1:6.8:5.4 to obtain an alkaline solution. Tetraethyl orthosilicate was dissolved in ethanol in a mass ratio of 1:10.8 to prepare a tetraethyl orthosilicate solution. The mixture was stirred continuously. The tetraethyl orthosilicate solution was added dropwise to the alkaline solution in a mass ratio of 0.1:1 for 20 min. After the addition was complete, the mixture was stirred at 50℃ and 500 r / min for 8 h until the solution turned milky white. The mixture was centrifuged at 12000 rpm for 2 min. The product was washed 5 times alternately with EtOH and high-purity water to obtain silica nanoparticles.
[0125] S2. Silica nanoparticles were dispersed in a dispersion medium to obtain a dispersion with a concentration of 10 wt%. At a mass ratio of surface modifier to tetraethyl orthosilicate of 0.12:1, the surface modifier (GPTMS:APTES mass ratio = 1:1.92) was added dropwise to the dispersion at 500 r / min. After the addition was complete, the reaction temperature was maintained at 90℃ for 4 h. After the reaction was completed, the mixture was centrifuged at 12000 rpm for 10 min. The product was washed three times with EtOH and dried in a vacuum environment at 80℃ for 4 h to obtain modified silica nanoparticles.
[0126] S3. At 1500 r / min, magnesium chloride hexahydrate and sodium hydroxide were mixed at a mass ratio of 4.3:1 and stirred at 95℃ for 1.5 h. After the reaction was completed, the mixture was centrifuged at 12000 rpm for 2 min. The product was washed 8 times with high-purity water and then 3 times with EtOH to obtain magnesium hydroxide nanoparticles.
[0127] S4. With a concentration of 10 wt% for magnesium hydroxide nanoparticles, magnesium hydroxide nanoparticles were ultrasonically dispersed in an aqueous solution of 0.6 wt% dispersion medium (chitosan) to obtain a magnesium hydroxide nanoparticle dispersion.
[0128] S5. At room temperature, modified silica nanoparticles were dispersed in high-purity water to obtain an aqueous phase of modified silica nanoparticles with a concentration of 11.5 wt%; magnesium hydroxide nanoparticle dispersion was dispersed in high-purity water to obtain an aqueous phase of magnesium hydroxide nanoparticles with a concentration of 5 wt%.
[0129] The modified silica nanoparticles and magnesium hydroxide nanoparticles were mixed with an oil phase containing 0.5 wt% crosslinking agent (terephthaloyl chloride) at a mass ratio of 1:3, and the total volume ratio of the modified silica nanoparticle aqueous phase and the magnesium hydroxide nanoparticle aqueous phase to the oil phase containing the crosslinking agent was 1:2. The mixture was ultrasonicated for 2 h, and excess liquid was removed after ultrasonication to obtain a silica nanoparticle emulsion flame retardant.
[0130] Comparative Example 1
[0131] This embodiment provides a method for preparing an emulsion flame retardant.
[0132] The difference from Example 1 is that in this comparative example, S1 is not performed, and the silica nanoparticles in step S2 are replaced with an equal mass of magnesium hydroxide nanoparticles.
[0133] Comparative Example 2
[0134] This embodiment provides a method for preparing an emulsion flame retardant.
[0135] The difference from Example 1 is that in this comparative example, S3 is not performed, and the magnesium hydroxide nanoparticles in step S4 are replaced with an equal mass of silicon dioxide nanoparticles.
[0136] Performance Test 1:
[0137] The performance of the flame retardants provided in the examples and comparative examples was tested using the following methods:
[0138] Take 20 g of coal sample with an average particle size of approximately 10 mm (obtained from Sandaogou Coal Mine, Fugu County, Yulin City, Shaanxi Province, after crushing and passing through a 1-mesh sieve). Spray 2 g of emulsion onto the coal sample for coal blending. Using a programmed temperature rise experiment, the temperature is increased to 150℃ at a rate of 2℃ / min. The CO concentration is measured to calculate the flame retardancy rate of the emulsion on the coal sample.
[0139] Flame retardancy rate of coal sample = (CO release from untreated coal sample - CO release from flame retardant-treated coal sample) ÷ CO release from untreated coal sample × 100%.
[0140] The test results are as follows:
[0141] Table 1
[0142]
[0143] As can be seen from the examples and performance tests, the silica nanoparticle emulsion flame retardant provided by the present invention has excellent flame retardant effect, wherein the flame retardant rate is ≥50%, and within the preferred range, the flame retardant rate is ≥80%.
[0144] Performance Test 2:
[0145] The silica nanoparticle emulsion flame retardant provided in Example 1 was diluted (the amount after dilution was the same as in Performance Test 1, i.e., 2 g of diluted solution was used), and the test was conducted according to the test method of Performance Test 1. The results are as follows:
[0146] Table 2
[0147]
[0148] As shown in Table 2, the silica nanoparticle emulsion flame retardant provided by this invention still exhibits excellent flame retardant effects even after dilution. That is, the silica nanoparticle emulsion flame retardant provided by this invention can be applied directly or after dilution. After dilution, the fluidity of the emulsion increases, which allows the effective flame retardant components to spread more evenly on the surface of the coal sample. Therefore, the flame retardant still exhibits excellent flame retardancy even after dilution. At the same time, dilution can reduce the amount of flame retardant used, thereby reducing the application cost of the flame retardant.
[0149] Performance Test 3
[0150] The silica nanoparticle emulsion flame retardant provided in Example 1 was used after being left to stand for a period of time, and the test was conducted according to the test method of Performance Test 1. The results are as follows:
[0151] Table 3
[0152]
[0153] As shown in Table 3, the silica nanoparticle emulsion flame retardant provided by the present invention has excellent storage stability, and its flame retardant effect remains good even after standing for more than 15 days.
[0154] The present invention has been illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A silica nanoparticle emulsion flame retardant, characterized in that, It includes: an aqueous phase of modified silica nanoparticles, an aqueous phase of magnesium hydroxide nanoparticles, and an oil phase containing a crosslinking agent.
2. The silica nanoparticle emulsion flame retardant according to claim 1, characterized in that, The particle size D50 of the modified silica nanoparticles is 10-500 nm, preferably 10-100 nm; And / or, the modified silica nanoparticles are surface-modified silica nanoparticles, preferably the surface modifiers include 3-aminopropyltriethoxysilane and / or 3-glycidoxypropyltrimethoxysilane; And / or, the concentration of the aqueous phase of the modified silica nanoparticles is 1-25 wt%, preferably 3.5-11.5 wt%.
3. The silica nanoparticle emulsion flame retardant according to claim 1 or 2, characterized in that, The particle size D50 of the magnesium hydroxide nanoparticles is 10-500 nm, preferably 10-100 nm; And / or, the aqueous phase of the magnesium hydroxide nanoparticles further includes a dispersion medium, preferably the dispersion medium includes any one or a combination of at least two of sodium alginate, chitosan or polyethyleneimine; And / or, the mass ratio of the modified silica nanoparticles to magnesium hydroxide nanoparticles is 1:(0.1-10), preferably 1:(0.4-8).
4. The silica nanoparticle emulsion flame retardant according to any one of claims 1-3, characterized in that, The crosslinking agent includes any one or a combination of at least two of adipoyl chloride, phthaloyl chloride, isophthaloyl chloride or terephthaloyl chloride, preferably terephthaloyl chloride; And / or, in the oil phase containing the crosslinking agent, the concentration of the crosslinking agent is 0.1-5 wt%; And / or, the total volume ratio of the aqueous phase of the modified silica nanoparticles and the aqueous phase of the magnesium hydroxide nanoparticles to the volume ratio of the oil phase containing the crosslinking agent is 1:(1-20), preferably 1:(2-5).
5. The silica nanoparticle emulsion flame retardant according to any one of claims 1-4, characterized in that, The flame retardancy of the silica nanoparticle emulsion flame retardant is ≥40%, preferably ≥45%, and more preferably ≥53%.
6. A method for preparing a silica nanoparticle emulsion flame retardant as described in any one of claims 1-5, characterized in that, The preparation method includes: The modified silica nanoparticle aqueous phase, magnesium hydroxide nanoparticle aqueous phase, and oil phase containing a crosslinking agent are mixed and reacted. After the reaction, excess liquid is removed to obtain the silica nanoparticle emulsion flame retardant.
7. The preparation method according to claim 6, characterized in that, The silica nanoparticles are prepared by a sol-gel method, preferably including: hydrolysis and condensation of tetraethyl orthosilicate under an alkaline catalyst to obtain the silica nanoparticles.
8. The preparation method according to claim 7, characterized in that, The method for preparing the modified silica nanoparticles includes: mixing silica nanoparticles with a surface modifier and reacting them to obtain the modified silica nanoparticles; Preferably, the mass ratio of the surface modifier to the tetraethyl orthosilicate is (0.5-15):1, more preferably (0.8-12):1; Preferably, the reaction temperature is 65-90℃ and the time is 4-12 h.
9. The preparation method according to any one of claims 6-8, characterized in that, The preparation method of the magnesium hydroxide nanoparticles is a liquid-phase coprecipitation method, preferably including: a mixed reaction of magnesium chloride hexahydrate and sodium hydroxide to obtain the magnesium hydroxide nanoparticles; Preferably, the stirring rate of the reaction is 1000-1200 r / min, the temperature is 70-95℃, and the time is 1.5-4 h; Preferably, the method for preparing the aqueous phase of magnesium hydroxide nanoparticles includes: mixing magnesium hydroxide nanoparticle dispersion with pure water to obtain the aqueous phase of magnesium hydroxide nanoparticles; Preferably, the preparation method of the magnesium hydroxide nanoparticle dispersion includes: mixing magnesium hydroxide nanoparticles and a dispersion medium in water to obtain the magnesium hydroxide nanoparticles.
10. The application of a silica nanoparticle emulsion flame retardant as described in any one of claims 1-5 in coal spontaneous combustion prevention and extinguishing materials.